Innovation of Islamic wasathiyah education methods: Transformation of da’wah in the contemporary era - Syafii, Imam (Indonesian Research Journal in Education |IRJE|, 2025)
This study examined the innovative Islamic wasathiyah learning methods at Al-Akbar Mosque, Surabaya, which emphasize moderation, balance, and inclusiveness, and integrate the values of tolerance and anti-extremism. Qualitative-descriptive method with participatory observation techniques, in-depth interviews, and document studies was used. The educational approach at Al-Akbar Mosque involved various methods, ranging from one-way teaching to multi-directional discussions, maintaining local traditions that align with Islamic teachings. Worship practices such as congregational dhikr, congregational prayers, and commemoration of Islamic holidays were used, GenZi studies that reflect the constructive spirit of Islamic wasathiyah, and supporting facilities such as eco-green playmates, general poly, dental poly, cupping therapy, and Islamic education institutions (PAUD, MI, Madrasah Aliyah and Ma'had Ali). Other facilities, such as urban farming, Civilization Park, Asmaul Husna Park, Healthy Heart Club, and Gen Z Park were used, which support social, health, and educational activities, hope to contribute theoretically and practically to the development of adaptive mosque da'wah and strengthen Islamic wasathiyah in Indonesia.